2010
DOI: 10.1111/j.1439-0434.2009.01605.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission ofPepino mosaic virusby the Fungal VectorOlpidium virulentus

Abstract: Transmission of Pepino mosaic virus by the Fungal Vector Olpidium virulentus A Ana na A Alfaro lfaro-F -Fernandez erná ndez, , M Marıa aría del del C Carmen armen C Cordoba ó rdoba-S -Selles ellés, , J Jose osé A Á ngel ngel H Herrera errera-V -Vasquez á squez, , M Marıa del aría del C Carmen armen C Cebrian ebriá n and and C Concepcion oncepció n J Abstract Transmission of Pepino mosaic virus (PepMV) by the fungal vector Olpidium virulentus was studied in two experiments. Two characterized cultures of the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 25 publications
(47 reference statements)
0
18
0
1
Order By: Relevance
“…Alfaro-Fernández et al (11) reported that PepMV-EU can reach a transmission rate of 8% when healthy tomato plants are irrigated with drainage water collected from PepMV-EU-infected plants when their roots contain the fungal vector Olpidium virulentus. However, drainage water obtained from vector-free PepMV-EU-infected plants did not result in transmission of this virus to healthy tomato plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alfaro-Fernández et al (11) reported that PepMV-EU can reach a transmission rate of 8% when healthy tomato plants are irrigated with drainage water collected from PepMV-EU-infected plants when their roots contain the fungal vector Olpidium virulentus. However, drainage water obtained from vector-free PepMV-EU-infected plants did not result in transmission of this virus to healthy tomato plants.…”
Section: Discussionmentioning
confidence: 99%
“…PepMV can survive and remain infectious for several weeks in plant debris and on contaminated surfaces (10). To date, information on water-mediated transmission of PepMV has only been available for genotype PepMV-EU (11,12). PVY NTN isolates are the main cause of potato tuber necrotic ring spot disease (13), which is one of the greatest problems in potato production.…”
mentioning
confidence: 99%
“…It is suggested that this coiled-coil might mediate the interaction between 2b and CPs. Species in the chytrid genus Olpidium transmit viruses with isometric particles, with the exception of the potexvirus PepMV being transmitted by O. virulentus (Alfaro-Fernández et al, 2010), while species in two plasmodiophorid genera (Polymyxa and Spongospora) transmit rod-shaped or filamentous viruses (Table 12.8). Rochon et al, 2004) Several viruses are transmitted by soil-inhabiting fungi or protists.…”
Section: B Tobravirusesmentioning
confidence: 99%
“…(HerreraVasquez et al 2009). Molecular identification has allowed the determination of O. brassicae as a vector of OMMV (Varanda et al 2011b) and O. virulentus as a vector of Tobacco stunt virus, Pepino mosaic virus, of a dianthovirus causing the necrotic streak of fique and of Mirafiori lettuce big-vein virus and Lettuce big-vein associated virus (Sasaya and Koganezawa 2006;Alfaro-Fernandez et al 2010;Gonzalez et al 2010;Maccarone et al 2010).…”
mentioning
confidence: 99%